Rapidly progressive coronary aneurysm: a rare case of isolated coronary vasculitis with recurrent myocardial infarction - Rodrigues, Tiago (2022)
© 2022 The Authors. Published by Elsevier on behalf of the American College of Cardiology Foundation. This article is available under the Creative Commons CC-BY-NC-ND license and permits non-commercial use of the work as published, without adaptation or alteration provided the work is fully attributed.